Antioxidant Activities in vitro of Water and Liposoluble Extracts Obtained by Different Species of Edible Insects and Invertebrates - Di Mattia, Carla; Battista, Natalia; Sacchetti, Giampiero; Serafini, Mauro (Frontiers in Nutrition, 2019)
A new global interest in entomophagy, the practice of eating insects, and invertebrates, arise from the impellent necessity of preserving agriculture resources and to obtain a drastic reduction of the ecological impact of animal food on the planet. The composite nutritional content, direct consequences of a plant-based feeding, associated with the undoubtedly ecological properties, suggest for insects a role as sustainable and functional foods. We aim to investigate the ability of water and liposoluble extracts, obtained by 12 commercially available edible insects and two invertebrates, to display an antioxidant effect in vitro. Results show that water-soluble extracts of grasshoppers, silkworm, and crickets display the highest values of antioxidant capacity (TEAC), 5-fold higher than fresh orange juice, while evening cicada, giant water bugs, Thai zebra tarantula, and black scorpions have negligible values. Grasshoppers, African caterpillars, and crickets have the highest levels of reducing power (FRAP), double than fresh orange juice. Grasshoppers, black ants, and mealworms contain the highest levels of total polyphenols, while Thai zebra tarantula, black scorpions, and giant water bugs are positioned at the bottom of the ranking. The liposoluble fraction of silkworm, evening cicada, and African caterpillars shows highest level of TEAC, twice than olive oil, while Thai zebra tarantula, palm worm, and black ants are placed at the bottom of the ranking. Edible insects and invertebrates represent a potential source of antioxidant ingredients with an efficiency related to their taxonomy and eating habits. More evidences are needed in order to understand if the practice of eating insects and invertebrates might contribute to modulate oxidative stress in humans.